Risk factors control for primary prevention of cardiovascular disease in men: Evidence from the Aragon Workers Health Study (AWHS) - Aguilar-Palacio, Isabel (PLoS One, 2018)
Benefits of cardiovascular disease (CVD) risk factors control are well known, but goals achievement remains low. The objective of this study is to evaluate the prevalence of CVD risk factors among men ina worker’s cohort with no previous CVD, to study control variations across time and the factors associated with poor control. To this end, we conducted a cohort reexamination (2010–2014) within the context of the Aragon Workers Health Study (AWHS). Data from working characteristics, analytical values and pharmacological prescription were included in the analysis. Prevalences of risk factor diagnosis and control were calculated, as well as factors associated with poor control. The prevalence of CVD risk factors was high. In 2014dyslipidaemia was the most prevalent (85.2%) followed by Hypertension (HT) (42.0%). People under treatment increased for the period analysed (p<0.001). The proportion of people treated varied from 72.2% in Diabetes Mellitus to 31.1% in dyslipidaemia in 2014. 46.2% of the workers with HT were controlled, decreasing to 21.9% in Diabetes and 11.0% in dyslipidaemia (2014). Working in a turn different to central shift was associated with poor control, especially for those working at night with HT (Odds Ratio in 2010: 3.6; Confidence Interval 95% 1.8–7.4) and dyslipidaemia (Odds Ratio 2010: 4.7; Confidence Interval 95% 1.3–16.4). We conclude that, although CVD control has increased significantly for the period studied, there are still many people that do not receive any treatment, and control goals are normally not achieved.